2016
DOI: 10.1080/14786419.2016.1263847
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from aerial parts of Annona senegalensis against Streptococcus mutans

Abstract: Antimicrobial potential of medicinal plants have been explored extensively these days. This study was carried out to evaluate the antibacterial potential from aerial parts of plant, called 'Annona senegalensis' and its constituents. Bioassay guided fractionation led to the isolation of four metabolites, (+)-catechin (1), (-)-anonaine (2), (-)-asimilobine (3) and (+)-nornantenine (4). This is the first report on the isolation of compounds 1, 3 and 4 from this plant. Compounds 2 and 4 showed good activity, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The study identified acetogenin and annosenegalin from the seed extract of Annona senegalansis and annogalene; gigantetronenine; squamocine; glaucanisine; glaucanetine; goniothalamicine from the root extract. Six alkaloids were also found out, namely roemerine; anonaine; nornuciferine; liriodenine; coclaurine; isoboldine, from the leave extract of Annona senegalensis [42][43][44][45][46].…”
Section: Annona Senegalensismentioning
confidence: 99%
“…The study identified acetogenin and annosenegalin from the seed extract of Annona senegalansis and annogalene; gigantetronenine; squamocine; glaucanisine; glaucanetine; goniothalamicine from the root extract. Six alkaloids were also found out, namely roemerine; anonaine; nornuciferine; liriodenine; coclaurine; isoboldine, from the leave extract of Annona senegalensis [42][43][44][45][46].…”
Section: Annona Senegalensismentioning
confidence: 99%
“…In a similar research lee et al revealed that S. mutans biofilm had the highest level of sensitivity for the extract of Sophora flavescens (45). Furthermore, several studies aimed at investigating the anti-bacterial and anti-biofilm activities of pure phytochemicals and some compounds such as linoleic, linolenic, oleanolic, betulinic acids, betulin, beta-sitosterol glucoside and carvacrol introduced as effective compounds against dental caries development and S. mutans biofilm formation (16,46,47). Due to costly and time consuming of convention methods for evaluation, drug likeness and anti-bacterial activities of phytochemicals currently in silico methods have been regarded.…”
Section: Discussionmentioning
confidence: 99%
“… Plant names Family Antiviral activities References Sutherlandia frutescens Fabaceae HIV1 RT, IN, RNase H Bessong et al., (2005) , 2006 ; Harnett et al., (2005) Prunus africana Rosaceae CMV Tolo et al., (2007) Carissa edulis Apocynaceae HSV-1 CDV, CPIV, FHV, LSDV PV-2 CMV Mukhtar et al. (2008) ; Tolo et al., (2006) Bagley (2018) Al-youssef and Hassan (2014) Tolo et al., (2007) Elaeodendron transvaalense Celastraceae HIV-1, RT, CB, IN Tshikalange et al., (2008) ; Bessong et al., (2005) , 2006 Terminalia sericea Combretaceae HIV1 RT HIV-1 RNA-dependent-DNA polymerase (RDDP) Tshikalange et al., (2008) Bessong et al., (2005) Crinum macowanii Amaryllidaceae HIV-1 RT, PR Klos et al., (2009) Ziziphus mucronata Rhamnaceae HIV-1 RT, RNase H Bessong et al., (2005) Helichrysum aureonitens Asteraceae HSV-1, reovirus Meyer et al., (1997) Euclea natalensis Ebenaceae HSV-1 Lall et al., (2017) Senna petersiana Fabaceae HIV1-RT Tshikalange et al., (2008) Adansonia digitata Malvaceae HSV-1 NDV HSV-1; ASFV HIV1 RT, HIV-FRET, PR Rathore et al., (2007) S...…”
Section: Methodsmentioning
confidence: 99%